Politician trojan horse issue: The challenge of developing a priority political strategy for facing the 2024 simultaneous elections - Ndona, Yakobus; Siagian, Liber; Ginting, Elisa Br; Faimau, Gabriel (Universitas Negeri Yogyakarta, 2025)
This article examines the concept of